Does the average (arithmetic mean) of a,b, and c equal c?
1. c-a = c+b
I'm sure this is a joke question for some of you but can someone dumb down their answer/explanation for me on this one? I don't know the best way to tackle it. And the kaplan
explanation is just not sinking in. thanks...
We need to see if (a+b+c)/3 = c
From stmt 1 we get a+b=0, nothing is known about c so insuff.
From stmt 2 we get c = 0 but nothing is known about a,b so insuff.
Combing we have all information for a,b and c. So this is suff.